TCR Repertoire Analysis by Next Generation Sequencing Allows Complex Differential Diagnosis of T Cell–Related Pathology. Issue 11 (10th September 2013) - Dziubianau, M.; Hecht, J.; Kuchenbecker, L.; Sattler, A.; Stervbo, U.; Rödelsperger, C.; Nickel, P.; Neumann, A. U.; Robinson, P. N.; Mundlos, S.; Volk, H.‐D.; Thiel, A.; et al.
Abstract: Clonotype analysis is essential for complete characterization of antigen‐specific T cells. Moreover, knowledge on clonal identity allows tracking of antigen‐specific T cells in whole blood and tissue infiltrates and can provide information on antigenic specificity. Here, we developed a next generation sequencing (NGS)‐based platform for the highly quantitative clonotype characterization of T cells and determined requirements for the unbiased characterization of the input material (DNA, RNA, ex vivo derived or cell culture expanded T cells). Thereafter we performed T cell receptor (TCR) repertoire analysis of various specimens in clinical settings including cytomegalovirus (CMV), polyomavirus BK (BKV) reactivation and acute cellular allograft rejection. Our results revealed dynamic nature of virus‐specific T cell clonotypes; CMV reactivation was linked to appearance of new highly abundant antigen‐specific clonalities. Moreover, analysis of clonotype overlap between BKV‐, alloantigen‐specific T cell–, kidney allograft‐ and urine‐derived lymphocytes provided hints for the differential diagnosis of allograft dysfunction and enabled appropriate therapy adjustment. We believe that the established approach will provide insights into the regulation of virus‐specific/anti‐tumor immunity and has high diagnostic potential in the clinical routine. Abstract : This study describes the development and characterization of T cell receptor repertoire analysis based on Next Generation Sequencing and its application for complex differential diagnosis of posttransplant kidney dysfunction.